Potential Nephrotoxicity of Lisinopril and Valsartan on Patients with Congestive Heart Failure - Sarini Pani; Melisa I. Barliana; Eli Halimah; Venice Chaeriadi; Mally G. Sholih (Universitas Padjadjaran, Indonesia)
Lisinopril (angiotensin converting enzyme inhibitor) and valsartan (angiotensin II receptorblocker) are the first-line treatment for patients with congestive heart failure (CHF). Thesetwo drugs potentially cause side effects on renal functions. However, limited informationwas available regarding the comparison of potential nephrotoxicity of these drugs in IndonesianCHF patients. This research was aimed to compare the potential nephrotoxicitybetween lisinopril and valsartan in outpatients with CHF at a hospital in Palu, Indonesia.This was an observational study conducted during April-May 2015. Potential nephrotoxicitywere assessed by measuring serum creatinin (SCr) and blood urea nitrogen (BUN). Datawere obtained from Cardiology Unit from a hospital in Palu, Indonesia. Statistical analysiswas conducted using T-test and Mann-Whitney test. The increasing trend of SCr and BUNwere observed in lisinopril-treated patients with the mean of increase were 21% and 59%,respectively. Relatively higher increase was observed in valsartan treatment group with 47%and 51% in SCr and BUN, respectively. The analysis showed that there were significant differencesin SCr level between lisinopril and valsartan groups (p=0.001), but the oppositeresults observed in BUN parameter (p=0.697). Therefore, valsartan was potentially morenephrotoxic than lisinopril based on the increase of SCr parameter. Thus, lisinopril is recommendedfor CHF patients who are particularly at high risks of having renal impairment.Keywords: lisinopril, valsartan, nephrotoxicity, congestive heart failure